Costa Rica Case Study : Primary Health Care Achievements and Challenges within the Framework of the Social Health Insurance - Montenegro Torres, Fernando (World Bank, Washington, DC, 2013)
The objective of this paper is to assess the key interventions Costa Rica has developed to expand health coverage for the poor and other vulnerable groups, with an emphasis on its approach to primary health care. Universal health coverage in Costa Rica is provided through a single national health insurance program. This program, which protects the poor without the pitfalls of a fragmented system, and the sustained policies that have enabled the building of a solid primary health care system, is broadly recognized as a success story. At the same, time new challenges are emerging to sustaining the success of Costa Rica's universal health coverage. Social Security of Costa Rica (Caja Costarricense de Seguridad Social, CCSS) faces increased production costs and demographic and epidemiological changes in a rapidly aging population. This report is divided into three broad sections: (1) objective of the case study and health system overview; (2) primary health care and the organization of health services within CCSS; and (3) agenda of key policy decisions for a renewed primary health care approach as part of a more responsive and sustainable health insurance system.